Comparison of Weight Reduction and Water Loss for Convective and Osmo-convective Dehydrated Breadfruit (Artocarpus altilis (Parkinson) Fosberg) - Mas, Muhammad Abdurrahman; Larasati, Laurensia Citra (Indonesia International Institute for Life Sciences, 2022)
Breadfruit (Artocarpus altilis (Parkinson) Fosberg), a tropical fruit commonly found in Indonesia, contains a well balanced nutritional content. However, breadfruit has a rapid respiration rate which causes the fruit to be underutilized, leading to breadfruit becoming food waste. Convective dehydration is an effective method in slowing down the respiration rate, however, heat exposure can reduce the nutritional content of the breadfruit. The combination of osmotic pre-treatment and convective dehydration act as an alternative to achieve a similar outcome with a shorter amount of thermal exposure. This study aims to perform a study in determining the effectiveness of an osmotic treatment with 50° Brix sugar solution compared to convective dehydration on breadfruit. The results indicate that as expected, the weight reduction (WR) of the osmo-convective samples is lower where the WR is 80.680% for convective dehydrated samples and 57.190% osmo-convective dehydrated samples. The water loss (WL) is statistically similar where WL of osmo-convective dehydrated samples was 18.315% compared to WL of the convective dehydrated samples 19.836%. The higher WR in the osmo-convective treatments show that there is sugar uptake into the fruit, while the similar water loss indicates the same reduction in moisture content between treatments. These results show the potential benefit of applying osmo-convective treatments to breadfruit. However, the research is still in the early stages of development. There are additional parts of the research and parameters that need to be optimized and explored in the future.